ENGINEERING DESIGN OF AUTOMATIC SELENOID STOVE TO REDUCE MUSCULOSKELETAL DISORDERS COMPLAINTS USING NBM AND RULA APPROACH - Tri Wahyudi; Ratih Rahmawati; Silvia Uslianti (Center for Study and Journal Management FTI UMI, 2020)
UKM Kenanga is a home industry producing various cassava chips based in Kubu Raya district, West Kalimantan. Complaints regarding musculoskeletal were identified in the process of frying chips. The complaints were carpal tunnel syndrome, low back pain, neck pain, as well as on the forearm and upper arm. Non-ergonomic working position contributes to these complaints. Therefore, it is necessary to perform this analysis and suggest a tool that would be helpful to reduce the worker’s complaints. Formerly, there haven’t been any early studies that cover the design of an automatic stove for the frying process based on biomechanical considerations, particularly on musculoskeletal disorder complaints.This study performs an analysis based on Nordic Body Map (NBM) and Rapid Upper Limb Assessment (RULA) concerning the process of frying the chips. Nordic Body Map analysis was used to identify body parts that were experiencing fatigue. Following the Nordic Body Map results, the automatic stove was designed to solve the employees’ complaints. RULA approach was used to analyze the condition after the employees carried out the work using the stove. The outcomes of this study are an automatic solenoid stove and a stool for the process of chips frying. RULA approach on the frying process with the manual stove and with the automatic solenoid stove resulted in L4-LV compression level reduced by 71.05%, whereas for Flex/Ext Compression was 87.97%